Echocardiographic abnormalities and determinants of 1-month outcome of stroke among West Africans in the SIREN Study (2019)
Background-—Little is known about the relationship between echocardiographic abnormalities and outcome among patients with acute stroke. We investigated the pattern and association of baseline echocardiographic variables with 1-month disability and mortality among patients with stroke in the SIREN (Stroke Investigative Research and Education Network) study. Methods and Results-—We enrolled and followed up consecutive 1020 adult patients with acute stroke with baseline transthoracic echocardiography from west Africa. To explore the relationship between echocardiographic variables and 1-month disability (using modified Rankin scale >3) and fatality, regression models were fitted. Relative risks were computed with 95% CIs. The participants comprised 60% men with a mean age of 59.2_14.6 years. Ischemic stroke was associated with smaller aortic root diameter (30.2 versus 32.5, P=0.018) and septal (16.8 versus 19.1, P<0.001) and posterior wall thickness at systole (18.9 versus 21.5, P=0.004). Over 90% of patients with stroke had abnormal left ventricular (LV) geometry with eccentric hypertrophy predominating (56.1%). Of 13 candidate variables investigated, only baseline abnormal LV geometry (concentric hypertrophy) was weakly associated with 1-month disability (unadjusted relative risk, 1.80; 95% CI, 0.97–5.73). Severe LV systolic dysfunction was significantly associated with increased 1-month mortality (unadjusted relative risk, 3.05; 95% CI, 1.36–6.83). Conclusions-—Nine of 10 patients with acute stroke had abnormal LV geometry and a third had systolic dysfunction. Severe LV systolic dysfunction was significantly associated with 1 month mortality. Larger studies are required to establish the independent effect and unravel predictive accuracy of this association